FMMWCNTs@CPA@SMTU@PdII NPs: As a Versatile Ferromagnetic Nanostructured Catalyst for Sonogashira‐Hagihara Cross‐Coupling Reaction in Solvent‐Free Conditions. Issue 4 (30th January 2019) - Ghasemzadeh, Maryam Sadat; Akhlaghinia, Batool
Abstract: This study deals with the designing and preparation of Pd II immobilized on ferromagnetic multi‐walled carbon nanotubes functionalized by aminated 2‐chloroethylphosphonic acid with S ‐methylisothiourea (FMMWCNTs@CPA@SMTU@Pd II NPs) as a versatile ferromagnetic nanostructured catalyst. Fourier transform infrared (FT‐IR), X‐ray diffraction (XRD) analysis, transmission electron microscopy (TEM), field emission scanning electron microscopy (FE‐SEM), energy‐dispersive X‐ray spectroscopy (EDX), EDS‐map, thermogravimetric analysis (TGA), vibrating sample magnetometry (VSM), inductively coupled plasma atomic emission spectroscopy (ICP‐OES) and X‐ray photoelectron spectroscopy (XPS) were used to characterize the nanocatalyst. The results show that FMMWCNTs@CPA@SMTU@Pd II NPs with decorated MWCNTs by Fe3 O4 NPs exhibited ferromagnetic properties with a uniform rod‐like morphology and particle sizes of about 20–30 nm. The catalytic performance of FMMWCNTs@CPA@SMTU@Pd II NPs was evaluated in Sonogashira‐Hagihara cross‐coupling reaction at room temperature and in solvent‐free conditions. Under appropriate condition, all reactions proceeded at a faster initial rate while exhibiting excellent activity and selectivity and the desired products were obtained in relatively excellent yields. Abstract : Here, we have developed of Pd II immobilized on ferromagnetic multi‐walled carbon nanotubes functionalized by aminated 2‐chloroethylphosphonic acid with S ‐methylisothiourea (FMMWCNTs@CPA@SMTU@Pd II NPs) as an efficient nanocatalyst for Sonogashira‐Hagihara cross‐coupling reaction in solvent‐free conditions.